Post-Keynesian Essays from Down Under Volume II: Essays on Policy and Applied Economics Theory and Policy in an Historical Context - Harcourt, G.; Kriesler, Peter; Halevi, Joseph; Nevile, John (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Joseph Halevi, G. C. Harcourt, Peter Kriesler and J. W. Nevile bring together a collection of their most influential papers on post-Keynesian thought. Their work stresses the importance of the underlying institutional framework, of the economy as a historical process and, therefore, of path determinacy. In addition, their essays suggest the ultimate goal of economics is as a tool to inform policy and make the world a better place, with better being defined by an overriding concern with social justice. Volume II assess application and policies.